Pengaruh Model Pembelajaran Guided Discovery terhadap Peningkatan Hasil Belajar dan Efikasi Diri Peserta Didik - Nur Wahidah; Yusminah Hala; Muhammad Arsyad (Universitas Negeri Makassar, 2023)
This study is a quasi-experimental research that aims to examine whether there is an influence of Guided Discovery learning model on learning outcomes and students’ self-efficacy with pretest-posttest control group design. Data on learning outcomes were obtained through pre-test and post-test by giving a written test in the form of multiple choice questions with 30 questions, while self-efficacy data was also obtained through pre-test and post-test from filling out a self-efficacy questionnaire with 30 statements. The data analysis technique employed descriptive statistical analysis, N-Gain, and inferential with t test (independent sample test). The results of descriptive analysis show that (1) the learning outcomes of experimental class students are in moderate category. (2) for self-efficacy of experimental class students in moderate category. (3) the learning outcomes in the control class is in low category. (4) the students’ self-efficacy in the control class is in low category (5) the results of inferential statistical analysis show that there is a significant influence of implementing Guided Discovery learning model on the improvement of learning outcomes and self-efficacy of grade VIII students at SMPN Gollek No. 34 Selayar Islands.